2000
DOI: 10.1042/bj3450279
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic modulation of ryanodine binding to sarcoplasmic reticulum vesicles of skeletal muscle by Zn2+ ions

Abstract: With the use of a [$H]ryanodine binding assay, the modulation of skeletal muscle ryanodine receptor (RyR1) by Zn# + was investigated. In the presence of 100 µM free Ca# + concentration (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In addition, our present work demonstrated, for the first time, that an increase in [Zn 2+ ] i is associated with hyperphosphorylation of the RyR2 in a concentration-dependent manner, at most via phosphorylation of both PKA and CamKII under acute zinc-inophore ZnPT exposure rather than a direct hyperphosphorylaion of RyR2 with increased [Zn 2+ ] i . This hypothesis depending on our observations is further supported with the data on multiple functional effects of [Zn 2+ ] i on CaMKII and modulation of RyR1 binding to SR vesicles in skeletal muscle biphasically [48], [49]. Indeed, it is well-accepted that [Zn 2+ ] i level plays critical roles in the redox signaling pathway and maintaining the normal structure and physiology of various cell types [62].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, our present work demonstrated, for the first time, that an increase in [Zn 2+ ] i is associated with hyperphosphorylation of the RyR2 in a concentration-dependent manner, at most via phosphorylation of both PKA and CamKII under acute zinc-inophore ZnPT exposure rather than a direct hyperphosphorylaion of RyR2 with increased [Zn 2+ ] i . This hypothesis depending on our observations is further supported with the data on multiple functional effects of [Zn 2+ ] i on CaMKII and modulation of RyR1 binding to SR vesicles in skeletal muscle biphasically [48], [49]. Indeed, it is well-accepted that [Zn 2+ ] i level plays critical roles in the redox signaling pathway and maintaining the normal structure and physiology of various cell types [62].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it has been shown that Zn 2+ has multiple functional effects on Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) [48], [49] while divalent metal ions influence catalysis and active-site accessibility in the cAMP-dependent protein kinase [50]. In order to demonstrate possibility of higher phosphorylation levels of two different kinases (PKA and CaMKII) with increased intracellular Zn 2+ , which are responsible from hyperphosphorylation of RyR2 under pathological conditions, rather than a direct hyperphosphorylated-RyR2 with Zn 2+ , in another set of experiments, we measured the phosphorylation levels of both PKA and CaMKII (with respect to their protein levels) with ZnPT exposures, under in vitro conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Mg 2+ , Zn 2+ , NO, and ATP are known modulators of the RyR function (Xia et al. ; Lanner et al. ; Suhr et al.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained at the same time show that Zn 2+ has a biphasic modulatory effect on Ca 2+ regulatory sites on RYR (the channel does not pass into the active state unless a nmol concentration of Ca 2+ is present in its niche; it becomes inactive if Ca 2+ is present in concentrations greater than 1 μM). It should also be noted that the affinity of Ca 2+ on the binding sites changes significantly in the presence of Zn( 2+ ), whereas changes in Ca 2+ had no clear effect on the affinity of Zn 2+ on binding [ 64 ].…”
Section: Can Skeletal Muscle Be a Model For Testing The Hypothesis?mentioning
confidence: 99%